Recycling fish scale powder in improving the performance of asphalt: A sustainable utilization of fish scale waste in asphalt. (15th March 2021) - Lv, Songtao; Hu, Long; Xia, Chengdong; Cabrera, Milkos Borges; Guo, Yanpeng; Liu, Chaochao; You, Lingyun
Abstract: Limited non-renewable resources and deteriorating ecological environment have emphasized the significance of the effective utilization of biomaterials. Many studies have specified that fish scales (FS) possess potential applications as cleaner production in various industrial sectors. However, research on the effect of this eco-friendly and sustainable biomaterial on asphalt has not been reported. Thus, this study aims to investigate the effect of fish scale powder (FSP) on the performance of asphalt binders. Four types of fish scales modified asphalts (FSMA) were prepared by adding different contents of FSP to 70# base asphalt (4%, 8%, 12%, and 16% by weight of the base asphalt). Rotational viscometer (RV), dynamic shear rheometer (DSR), and bending beam rheometer (BBR) were employed to characterize the rheologic behavior of FSMA. The phase separation and sessile drop tests were carried out to evaluate the storage stability and adhesion of FSMA. In addition, the chemical characteristics were investigated by Fourier transform infrared (FTIR) spectroscopy. It was found that FSP enhanced the adhesion, viscoelastic properties, temperature susceptibility, and resistance to permanent deformation of asphalt. Moreover, it was discovered that FSP at low content had little effect on the aging, fatigue, and cracking resistance of the asphalt. Besides, there was a physical mixing between FSP and asphalt binder, and the mixture was a storage-stable product. Overall, it is promising and feasible to use FSP as a bio-modifier for asphalt binders and reduce waste treatment costs. This method is a sustainable utilization of fish scale waste.